Efficient methanol dehydration to DME and light hydrocarbons by submicrometric ZrO2-ZSM-5 fibrillar catalysts with a shell-like structure - Palomo-Jiménez, José; Rodríguez-Cano, Miguel Ángel; Berruezo-García, José; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2022)
Zeolites are widely used in many applications, such as catalysis and adsorption processes. The use of these materials in a nanometric size would be of great interest for these applications, due to the better performance they could exhibit in terms of avoiding intraparticle mass and heat transfer limitations. However, this small particle size results in high pressure drops in adsorption columns and fixed-bed reactors, making these materials non-applicable directly in the nanometric size. In this work, ZrO2 fibers with a mean diameter of 275 nm and the presence of small well-defined ZSM-5 zeolite aggregates of 550 nm in size around the ZrO2 submicrometric fibers, in the form of a shell-like structure, have been prepared by electrospinning technique, which resulted very active for the synthesis of DME and light olefins via methanol dehydration. The submicrometric fibrillar catalysts, without any further modification, could be easily structured inside a fixed-bed reactor, which worked very efficiently in terms of heat and mass transfer, avoiding, at the same time, the usual pressure drops problems of fixed-bed reactors working with catalyst particles of submicrometric size. Methanol conversion and selectivity to DME and light hydrocarbons could be finely controlled, for a given set reaction conditions, by tuning the zeolite loading in the structured catalyst. Apparent kinetic parameters for the selective methanol dehydration to DME were calculated assuming a reversible second order rate expression and an activation energy of 75 kJ/mol was obtained.
Keywords: Zeolitas; Core-shell; Dimethyl ether; Electrospinning; Zeolite; Fibers; Nanostructured catalysts